Validitas Lembar Kerja Mahasiswa Berbasis Connected Learning Cycle sebagai Upaya Peningkatan Keterampilan Proses Sains dan Keterampilan Literasi Sains - Rusmini, Rusmini; Suyono, Suyono; Agustini, Rudiana (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2024)
A study has been conducted on the development of Student Worksheets (LKM) based on Connected Learning Cycle (CLC) to improve Science Process Skills and Science Literacy. This study is included in the development research using the ADDIE model which is limited to the development stage. Validation is measured using a validation sheet assessed by five expert validators in the field of chemistry and chemistry education. It is said to be valid if it gets a very good mode. The data shows that the LKM developed received a very good assessment so that it can be said to be valid or worthy and can be continued to the trial stage for students. This study is useful as an effort to improve students' abilities in understanding science process skills and science literacy skills.